A Theoretical Study on Laser Cooling Feasibility of Group IVA Hydrides XH (X = Si, Ge, Sn, and Pb): The Role of Electronic State Crossing - Li, Donghui; Fu, Mingkai; Ma, Haitao; Bian, Wensheng; Du, Zheng; Chen, Congmei (Frontiers in Chemistry, 2020)
The feasibility of direct laser cooling of SiH, GeH, SnH and PbH is investigated and assessed based upon first principles. The internally contracted multireference configuration interaction method with the Davidson correction is applied. Very good agreement is obtained between our computed spectroscopic constants and the available experimental data. We find that the locations of crossing point between the B2Sigma- and A2Delta states have the tendency of moving downwards from CH to SnH relative to the bottom of the corresponding A2Delta potential, which precludes the laser cooling of GeH, SnH and PbH. By including the spin-orbit coupling effects and on the basis of the A2Delta5/2-> X2Pi3/2 transition, we propose a feasible laser cooling scheme for SiH using three lasers with wavelengths varying from 400 to 500 nm, which features a very large vibrational branching ratio (0.9954) and a very short radiative lifetime (575 ns). The importance of electronic state crossing in molecular laser cooling is underscored, and our work suggests useful caveats to the choice of promising candidates for producing ultracold molecules.